Writing History! : A Companion for Historians - Kamp, Jeanette; Legêne, Susan; Van Rossum, Matthias; Rümke, Sebas (Book collections on Project MUSE., 2018)
Historians not only have knowledge of history, but by writing about it and engaging with other historians from the past and present, they make history themselves. This companion offers young historians clear guidelines for the different phases of historical research; how do you get a good historical question? How do you engage with the literature? How do you work with sources from the past, from archives to imagery and objects, art, or landscapes? What is the influence of digitalisation of the historical craft? Broad in scope, 'Writing History!' also addresses historians? traditional support of policy makers and their activity in fields of public history, such as museums, the media, and the leisure sector, and offers support for developing the necessary skills for this wide range of professions.